Influence of electro-heating on the production of whey protein cold-set hydrogels - Pereira, Ricardo (2014)
Electro-heating has often been claimed to interfere with distribution of molecular secondary structure of whey protein isolate (WPI) networks due to the presence of a moderate electric field (MEF). Recently, cold gelation ability of WPI is also taking interest in protection and delivery of value-added bioactive compounds through micro and nano-association techniques. Hence, the aim of this work is producing cold-set hydrogels from WPI through combined application of an electro-heating treatment followed by cold gelation. Protein dispersions were heated under the absence and presence of MEF at denaturation temperatures (> 80 °C). Divalent iron cation (Fe2+) assisted cold gelation of electro-heated WPI and the effects of MEF on the produced hydrogels were reported and encouraged during this research. Nano-scale phenomena of WPI thermal aggregation as affected by applied MEF were assessed by dynamic light scattering technique. To shed more light on the produced protein hydrogels, samples were investigated by means of transmission electron microscopy and rheology techniques. Results shows that apparent viscosity values and protein aggregation decreased with increasing MEF intensity applied (i.e. treatments at 10 V/cm have determined an average particle sizes below 100 nm). Fe2+ addition resulted in the formation of a network mediated via interactions between cationic agents and WPI soluble aggregates. MEF and cold gelation can induces changes from a nanometer to micrometer range thus offering a great potential to the development of whey protein hydrogels with tailored mechanical and microstructural features Acknowledgments: Ricardo N. Pereira and Oscar L. Ramos gratefully acknowledge their Post-Doctoral grants (SFRH/BPD/81887/2011 and SFRH/BPD/80766/2011, respectively) by Fundação para a Ciência e Tecnologia (FCT, Portugal). The authors thank the FCT Strategic Project PEst-OE/EQB/LA0023/2013 and the project “BioInd - Biotechnology and Bioengineering for improved Industrial and Agro-Food processes", REF. NORTE-07-0124-FEDER-000028 Co-funded by the Programa Operacional Regional do Norte (ON.2 – O Novo Norte), QREN, FEDER.